EPS‐I polysaccharide protects Mycoplasma pulmonis from phagocytosis. Issue 2 (28th November 2012) - Shaw, Brandon M.; Daubenspeck, James M.; Simmons, Warren L.; Dybvig, Kevin
Abstract Few mycoplasmal polysaccharides have been described and little is known about their role in pathogenesis. The infection of mice with Mycoplasma pulmonis has been utilized in many in vivo and in vitro studies to gain a better understanding of host–pathogen interactions during chronic respiratory infection. Although alveolar macrophages have a primary role in host defence, M. pulmonis is killed inefficiently in vitro. One antiphagocytic factor produced by the mycoplasma is the family of phase‐ and size‐variable Vsa lipoproteins. However, bacteria generally employ multiple strategies for combating host defences, with capsular polysaccharide often having a key role. We show here that mutants lacking the EPS‐I polysaccharide of M. pulmonis exhibit increased susceptibility to binding and subsequent killing by alveolar macrophages. These results give further insight into how mycoplasmas are able to avoid the host immune system and sustain a chronic infection.